How is service procurement different from goods procurement? Exploring ex ante costs and ex post problems in IT procurement. Issue 2 (March 2018) - Wynstra, Finn; Rooks, Gerrit; Snijders, Chris
Abstract: Several studies suggest that, in practice, service procurement is more challenging than goods procurement. The underlying but largely implicit argument is that the procurement process for services involves higher buyer uncertainty and therefore requires extra efforts to mitigate this uncertainty. Drawing on Transaction Cost Economics, we use a database of information technology transactions to investigate the relationship between transaction characteristics and social embeddedness, and ex ante cost and ex post problems. We explore whether the same relationships hold across transactions that involve only goods versus transactions that also involve services. Our findings support conventional wisdom that managing the procurement process for transactions involving services is more challenging than for transactions involving goods. However, when controlling for typical transaction characteristics, there is no difference between transactions involving goods and transactions that also involve services. Highlights: One of the first studies to compare the execution of procurement activities for goods versus services. Managing the procurement process for service transactions is more costly and problematic. Classical transaction characteristics explain these transaction cost differences.